The Effective Impact of Integration of Body Oriented Psychotherapy, Spirituality, and Biofeedback Techniques on Discipline Troubled Students of Technical Training Institution - Norizan, Yusof; Muhammad Nubli, Abdul Wahab (Globeedu Group, 2017)
Multi-disciplinary integration of knowledge has been gaining traction from time to time. The contemporary techniques from a single discipline alone fall short in resolving myriads of conundrums and predicaments that are currently plaguing the society today. The social upheaval in today’s society is allegorical to a virulent cancer that is fast spreading among the society. This issue ought to be dealt with expeditiously through various approaches that are deemed pertinent in assisting the members of the society to function by playing their role aptly. This research introduces a particular intervention technique developed from the modules for troubled students in Technical Training Institute (ILT). The compiled technique from all expressive movement technique, known as Body Oriented Psychotherapy (BOP) is the state-of-the-art procedure introduced to Malaysia to be administered upon troubled individuals. In the effort to acclimatize said technique with dominant norm, belief and culture of Malaysia’s natives, spiritual Islamic elements are integrated into the technique, known as Spiritual Body Oriented Psychotherapy (SBOP). Said technique is also integrated with biofeedback technique to observe the impact on the student change. The effect of the techniques with and without the spiritual element is juxtaposed and evaluated. Both of techniques efficacies are tested against 56 students from Technical Training Institute in Kuantan. The resulting efficacies technique is evaluated through the relief enjoyed by the participants of the research. The finding of this research demonstrated that that both of the techniques namely, BOP and SBOP are effective in invoking relief upon the respondent, but SBOP showed better performance.